Periodic modulation in pulse arrival times from young pulsars: a renewed case for neutron star precession - Kerr, M.; Hobbs, G.; Johnston, S.; Shannon, Ryan (Oxford University Press, 2016)
In a search for periodic variation in the arrival times of pulses from 151 young, energetic pulsars, we have identified seven cases of modulation consistent with one or two harmonics of a single fundamental with time-scale 0.5–1.5 yr. We use simulations to show that these modulations are statistically significant and of high quality (sinusoidal) even when contaminated by the strong stochastic timing noise common to young pulsars. Although planetary companions could induce such modulation, the large implied masses and 2:1 mean motion resonances challenge such an explanation. Instead, the modulation is likely to be intrinsic to the pulsar, arising from quasi-periodic switching between stable magnetospheric states, and we propose that precession of the neutron star may regulate this switching.